Handbook of Issues in Criminal Justice Reform in the United States 2021
DOI: 10.1007/978-3-030-77565-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, Gender, and Economic Sentencing Disparity

Abstract: The presence of inequalities in criminal punishment according to defendants' race, ethnicity, gender, or socioeconomic status arguably challenges the philosophical and moral foundations of the justice system. Nevertheless, there is clear evidence of disproportional representation according to these offender characteristics in US correctional populations. For this reason, much criminological research over the past 50 years, and especially within the past two decades, has been devoted to examining judicial decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Notably, however, young Black males received lengthier prison sentences than White defendants regardless of gender and age. The observation that more pronounced racial/ethnic inequalities were present in the incarceration decision than in sentence length has been noted in several reviews of sentencing research (e.g., Baumer, 2013;Lehmann & Gomez, 2022;Mitchell, 2005;Spohn, 2000), with scholars positing that disparities in the latter outcome might be obfuscated by sentencing guidelines structures (Bushway & Piehl, 2001) or the unequal process of "cumulative disadvantage" resulting from decision-making at earlier justice system decision points (Kurlychek & Johnson, 2019;Kutateladze et al, 2014;Omori, 2019;Wooldredge et al, 2015).…”
Section: Sentencing Disadvantages For Young Black Malesmentioning
confidence: 92%
See 1 more Smart Citation
“…Notably, however, young Black males received lengthier prison sentences than White defendants regardless of gender and age. The observation that more pronounced racial/ethnic inequalities were present in the incarceration decision than in sentence length has been noted in several reviews of sentencing research (e.g., Baumer, 2013;Lehmann & Gomez, 2022;Mitchell, 2005;Spohn, 2000), with scholars positing that disparities in the latter outcome might be obfuscated by sentencing guidelines structures (Bushway & Piehl, 2001) or the unequal process of "cumulative disadvantage" resulting from decision-making at earlier justice system decision points (Kurlychek & Johnson, 2019;Kutateladze et al, 2014;Omori, 2019;Wooldredge et al, 2015).…”
Section: Sentencing Disadvantages For Young Black Malesmentioning
confidence: 92%
“…Though much scholarship reveals that mode of conviction is one of the strongest case-level correlates of sentencing outcomes, researchers also have long observed that defendants are punished in ways that are patterned according to their race/ethnicity. Indeed, hundreds of studies following this line of inquiry have been conducted over the past half-century, and comprehensive reviews of this body of work report consistent evidence of such disparities across a wide range of jurisdictions, sentencing structures, and defendant subpopulations (e.g., Baumer, 2013;Franklin, 2018;Lehmann & Gomez, 2022;Mitchell, 2005;Spohn, 2000;Ulmer, 2012). Notably, the finding that Black and-to a somewhat lesser extent-Hispanic defendants are disadvantaged at sentencing persists even after offense type, criminal history, prior case-processing decisions, local court context, and other similar factors are accounted for.…”
Section: Race/ethnicity Gender and Age Disparities In Sentencingmentioning
confidence: 99%